2022
DOI: 10.3389/fcvm.2022.804788
|View full text |Cite
|
Sign up to set email alerts
|

Rare Genetic Variants Associated With Myocardial Fibrosis: Multi-Ethnic Study of Atherosclerosis

Abstract: BackgroundRare pathogenic variants in cardiomyopathy (CM) genes can predispose to cardiac remodeling or fibrosis. We studied the carrier status for such variants in adults without clinical cardiovascular disease (CVD) in whom cardiac MRI (CMR)-derived measures of myocardial fibrosis were obtained in the Multi-Ethnic Study of Atherosclerosis (MESA).ObjectivesTo identify CM-associated pathogenic variants and assess their relative prevalence in participants with extensive myocardial fibrosis by CMR.MethodsMESA wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…7,8 MF can be a subclinical finding in HCM or sometimes it is the only pathophysiological manifestation as reflected by increased serum C-terminal propeptide of type I procollagen levels in HCM mutation carriers who do not yet have imaging evidence of hypertrophy. 7,8 We have also previously demonstrated that carrier status of rare pathogenic variants in 26 Although the prognostic role of MF has been well established in DCM, 27 its role in the risk for DCM has not been defined. The alternate alleles of the rs2186370 intronic variant identified in our study, A and G, are risk alleles for HCM and DCM, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 MF can be a subclinical finding in HCM or sometimes it is the only pathophysiological manifestation as reflected by increased serum C-terminal propeptide of type I procollagen levels in HCM mutation carriers who do not yet have imaging evidence of hypertrophy. 7,8 We have also previously demonstrated that carrier status of rare pathogenic variants in 26 Although the prognostic role of MF has been well established in DCM, 27 its role in the risk for DCM has not been defined. The alternate alleles of the rs2186370 intronic variant identified in our study, A and G, are risk alleles for HCM and DCM, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 We have also previously demonstrated that carrier status of rare pathogenic variants in cardiomyopathy-related genes in the MESA cohort who have not yet developed cardiomyopathies is more prevalent in individuals with CMR-detectable MF as compared with individuals with lower MF. 26 Although the prognostic role of MF has been well established in DCM, 27 its role in the risk for DCM has not been defined.…”
Section: Discussionmentioning
confidence: 99%
“…Although variants in cardiomyopathy-related genes are usually present in SCD cases due to inherited cardiomyopathies, such variants have also been associated with nonspecific subtle structural alterations ( e.g . myocardial fibrosis) 36, 44, 45 , and structurally normal hearts 46 . It has been hypothesized that variants in cardiomyopathy-related genes may contribute to SCA even without overt clinical signs of inherited cardiomyopathy, thus representing “concealed cardiomyopathy”.…”
Section: Discussionmentioning
confidence: 99%
“…ECV may also be sensitive to myocardial edema and inflammation, but such effects should be minimal because of the chronicity of alterations and the fact that it is a population of community dwellers, not patients. Additionally, our definition of interstitial fibrosis was somewhat arbitrary as the highest quartile since ECV is a continuous variable but is consistent with prior definitions used in MESA (30). Changing this definition could change the odds ratios but shouldn't qualitatively impact the differences between hs-cTnT and GDF-15 with ECV.…”
Section: Limitationsmentioning
confidence: 96%